Quality of life with and without sphincter-conserving surgery for rectal cancer: Calidad de vida con y sin cirugía conservadora de esfínteres por cáncer de recto - Segura González, José Manuel Carlos (2023)
Introduction: Colorectal cancer (CRC) is the third most common cancer and the second leading cause of death worldwide, with an incidence of 10.2%. The treatment of CRC has evolved over the past 25 years. Two surgical procedures are used: abdominoperineal resection (APR) and low anterior resection (LAR) and ultra-low anterior resection (ULAR). The recurrence rate and quality of life are similar between these approaches. Objective: To compare the quality of life of rectal cancer patients treated with abdominoperineal resection versus conservative sphincter-preserving surgeries: low anterior resection (LAR) and ultra-low anterior resection (ULAR) at UMAE of Puebla. Methods: A comparative, observational, cross-sectional study was conducted on CRC patients treated between 2015 and 2019 at a tertiary-level hospital in Puebla. Two groups were formed: those managed with APR and those managed with LAR/ULAR. The EORTC QLQ-CR29 scale and EuroQol were applied. Descriptive statistics and the Mann-Whitney U test were used for comparisons. Results: A total of 26 patients were recruited, 18 with APR and 8 with LAR/ULAR. The mean quality of life score in the APR group was 73.72 (SD 16.92, minimum 31.46, maximum 95.09), and in the LAR/ULAR group was 56.22 (SD 6.29, minimum 47.51, maximum 68.96), with a p-value of 0.005. Conclusions: There is no significant difference in the quality of life of CRC patients operated with APR, LAR, and ULAR (non-conservative and conservative approaches).